Dakshin Metal Products: Complexities of Channel Management - Dasari, Shailendra (Prabandhan: Indian Journal of Management, 2015)
This teaching case was developed for the students of sales and distribution management, an elective offered to the post graduate students of business management in most of the BSchools in India. All the characters in this case are fictitious, including the name of the company. The issues dealt with in the present case study are based on my experiences in various organizations that I have worked for. The gap between theory and practice and how lack of grass root knowledge of the market could be a major handicap, even for those who have impeccable credentials, formed the back drop of this case. This case would help students get better insights into various aspects of sales & distribution management.